The Effectiveness of Aid in Improving Regulations: Empirical evidence and the drivers of change in Rwanda - Matthias Busse; Ruth Hoekstra; Robert D. Osei (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2013)
The paper assesses the impact of foreign aid on the change in the quality of regulations, and identifies the drivers of this change in a case study on Rwanda. In the empirical analysis, we find that highly targeted Aid for Business has a significantly positive impact on regulations across developing countries, but we do not find any effects for overall aid or aid directed at broad governance areas. In the country case study, we depart from Rwanda's excellent regulatory performance to explain how aid is effective in changing the regulatory environment, driven by the country's strong political leadership and its singular institutional history.
Keywords: F35; G28; L51; O55; 330; Foreign aid; Governance; Business regulations; Rwanda; Entwicklungshilfe; Ausländisch; Regulierung; Good Governance; Wirkungsanalyse; Ruanda